General Public Awareness about the Indications and Complications of Sleeve Gastrectomy in Qassim Region, Saudi Arabia - Alolayan, Hayfa; Aldubayyan, Anwar; Aldhohayan, Asma; AlBassam, Rawaf; Almarzuqi, Shoug; Almoqaiteb, Taif; Almutlaq, Ghadah; Alquwayfili, Lubna (Open Access Macedonian Journal of Medical Sciences, 2021)
BACKGROUND: Sleeve gastrectomy has become prevalent worldwide regardless of the patient’s awareness about the indications and complications. That would affect their judgment and decision. AIM: This study aimed to assess the level of awareness about indications and complications of sleeve gastrectomy in the general public at Al-Qassim, Saudi Arabia in 2021. MATERIALS AND METHODS: This is a quantitative cross-sectional study conducted among the general public living in the Qassim region, Saudi Arabia. Using a convenience sampling technique to select the participants as a representative sample for the general population. The target population will include all Saudis, who live in Al-Qassim and aged above 18 years, and will exclude who does not live in al-Qassim, age under 18 years, non-Saudi, who does not complete the questionnaire and who refuse to participate. The data were collected using a validated self-administered questionnaire. Questionnaires include; demographic characteristics, general awareness about sleeve gastrectomy, and awareness toward the indication and complication of sleeve gastrectomy. All statistical analyses were performed using Statistical Packages for Software Sciences version 26. RESULTS: A total of 1091 respondents took part. The mean age of the respondents was 37.5 (SD 12.9) years old with females dominating the males (87.8% vs. 12.2%). Awareness about the indications and complications of sleeve gastrectomy constitutes 49% and 82.4%, respectively. In univariate analyses, those who have heard about body mass index (BMI) had greater knowledge of the indications and complications of sleeve gastrectomy. In a multivariate regression model, gender female was the independent significant predictor of sleeve gastrectomy complications whereas those who heard of BMI was the independent significant predictor of the knowledge toward the indications and complications of sleeve gastrectomy. CONCLUSION: The general public demonstrated a lack of knowledge regarding the indications of sleeve gastrectomy but their knowledge about complications was better. Better knowledge about BMI comes with a better awareness of the indications and complications of sleeve gastrectomy.